Hyperbaric oxygen treatment for chronic insomnia at high altitude: A prospective, randomized, open-label, parallel-group trial - Sun, Bin; He, Jinli; Chen, Haibo; Zeng, Wenming; Tian, Tingting; Abay, Mirebankez; Bian, Shizhu; Zhao, Junyong; Jin, Xia; Tan, Xiaofang; Zhu, Chaoan; Li, Dan; et al. (Travel medicine and infectious disease, 2025)
Hyperbaric oxygen (HBO) has been proposed to be effective for treating chronic insomnia at high altitudes. Patients suffering from chronic insomnia at high altitude were randomly assigned at a 1:1 ratio to either the hyperbaric oxygen (HBO) treatment group or the control group for a 10-day procedure. The primary outcome was insomnia status, which was assessed via the Pittsburgh Sleep Quality Index (PSQI) and the Insomnia Severity Index (ISI). The secondary outcomes included stratified comparisons of changes in the PSQI score and ISI score, Fatigue Severity Scale (FSS) score and Hospital Anxiety and Depression Scale (HADS) score. Analyses were performed for multiple comparisons for the primary outcomes at 2-sided 0.05 significance levels with Bonferroni corrections. A total of 80 patients were randomized in this study, and the median age was 25.0 years (IQR, 21.25–29.75). For the primary outcome of sleep quality, the PSQI score after treatment was significantly lower in the HBO group than in the control group (4.6 ± 3.15 vs. 9.1 ± 4.02; adjusted mean difference [aMD] −3.96 [-5.26 to −2.66], p < 0.0001). The ISI was also significantly lower in the HBO group than in the control group (5.0 ± 4.09 vs. 9.8 ± 6.47; aMD −4.10 [95 % CI, −5.68 to −2.51], p < 0.0001). For the secondary outcomes, the HBO group showed improvements in terms of fatigue, anxiety, and depression. No serious adverse events were reported in either group. HBO is an efficacious and safe treatment for chronic insomnia at high altitude. ChiCTR2100046917. •Hyperbaric oxygen treatment is effective for chronic insomnia at high altitude.•Hyperbaric oxygen treatment improved the fatigue and mental state of participants.•Hyperbaric oxygen is a safe physical treatment.